2019
DOI: 10.1186/s12933-019-0847-8
|View full text |Cite
|
Sign up to set email alerts
|

The combination of a neprilysin inhibitor (sacubitril) and angiotensin-II receptor blocker (valsartan) attenuates glomerular and tubular injury in the Zucker Obese rat

Abstract: ObjectiveDiabetic nephropathy (DN) is characterized by glomerular and tubulointerstitial injury, proteinuria and remodeling. Here we examined whether the combination of an inhibitor of neprilysin (sacubitril), a natriuretic peptide-degrading enzyme, and an angiotensin II type 1 receptor blocker (valsartan), suppresses renal injury in a pre-clinical model of early DN more effectively than valsartan monotherapy.MethodsSixty-four male Zucker Obese rats (ZO) at 16 weeks of age were distributed into 4 different gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 80 publications
3
43
0
Order By: Relevance
“…Improvement in the prognosis of patients assigned to sacubitril/valsartan also remained consistent in the subgroup of prediabetic, undiagnosed diabetic, and diagnosed diabetic patients, who are at a higher risk of adverse CV outcomes [53]. This evidence agrees with previous preclinical data demonstrating the cardio- and nephroprotective effects of ARNi [54,55,56,57].…”
Section: Clinical Applications Of Arnisupporting
confidence: 83%
“…Improvement in the prognosis of patients assigned to sacubitril/valsartan also remained consistent in the subgroup of prediabetic, undiagnosed diabetic, and diagnosed diabetic patients, who are at a higher risk of adverse CV outcomes [53]. This evidence agrees with previous preclinical data demonstrating the cardio- and nephroprotective effects of ARNi [54,55,56,57].…”
Section: Clinical Applications Of Arnisupporting
confidence: 83%
“…Emerging data showed that LCZ696 is more effective than valsartan therapy alone in delaying the progression of kidney disease via antiinflammation, antioxidant, and antifibrosis effects [33]. In early stages of diabetic nephropathy, Habibi et al [34] showed that LCZ696 was superior to valsartan in reducing proteinuria, renal ultrastructure, and tubular injury in a murine model. Furthermore, a recent study demonstrated that the renoprotection effect of LCZ696 was attributed by limiting podocyte injury [35].…”
Section: Discussionmentioning
confidence: 99%
“…Valsartan (Tabuvan®) and LCZ696 (EntrestoTM) tablets were suspended in 0.5% carboxymethyl cellulose (CMC) and administered by oral gavage in a volume of 0.5 ml/100 g body weight of each animal. For both medications, dose selection was based on previous literature 24 . During the experimental phase, the control and STZ groups were administered similar volumes of 0.5% CMC as the vehicle.…”
Section: Methodsmentioning
confidence: 99%